Fatigue performance rejuvenation of corroded 7075-T651 aluminum alloy through ultrasonic nanocrystal surface modification. (December 2021) - Zhang, Ruixia; Zhao, Weidong; Zhang, Hao; Yang, Wenjing; Wang, Guo-Xiang; Dong, Yalin; Ye, Chang
Graphical abstract: Highlights: UNSM repairs the corroded surface and induces compressive residual stresses. UNSM is effective in rejuvenating the fatigue life of corroded aluminum alloy. The fatigue life of the rejuvenated samples is comparable to the untreated ones. Abstract: In this study, ultrasonic nanocrystal surface modification (UNSM) was used to rejuvenate the fatigue performance of pre-corroded 7075-T651 aluminum alloy. The fatigue life of specimens subjected to pre-corrosion and burnishing was found to be only slightly higher than that of corroded specimens, while the fatigue life of the specimens subjected to pre-corrosion and UNSM treatment was twenty times higher than that of the corroded specimens. The findings of this study demonstrate that the repair of the corroded surface layer, surface work-hardening, and beneficial compressive residual stress induced by UNSM are responsible for the fatigue performance rejuvenation of the pre-corroded alloy.